Letter to Jane Tolmach; from Leslie H. Maland - Leslie H. Maland:::::: (1964)
Leslie H. Maland sent a letter to Jane Tolmach requesting for her presence in a new upcoming meeting of the Camarillo State Hospital Board of Trustees which I have called for Wednesday, November 25, 1964 at 12pm in Dr. Nash's office.